2022
DOI: 10.1021/acs.accounts.1c00678
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity in Electrochemical CO2 Reduction

Abstract: Conspectus The electrocatalytic CO2 reduction reaction (CO2RR) to generate fixed forms of carbons that have commercial value is a lucrative avenue to ameliorate the growing concerns about the detrimental effect of CO2 emissions as well as to generate carbon-based feed chemicals, which are generally obtained from the petrochemical industry. The area of electrochemical CO2RR has seen substantial activity in the past decade, and several good catalysts have been reported. While the focus was initially on the rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
155
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(157 citation statements)
references
References 53 publications
2
155
0
Order By: Relevance
“…Therefore, it is crucial to find ways to control selectivity. Recently, Saha et al [57] reported that the spin state of the metal center (M) in catalysts strongly affects the reaction pathway. As shown in Figure 4a, M-COOH is the key intermediate to CO or HCOOH.…”
Section: Carbon Dioxide Reduction Reaction (Co2rr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is crucial to find ways to control selectivity. Recently, Saha et al [57] reported that the spin state of the metal center (M) in catalysts strongly affects the reaction pathway. As shown in Figure 4a, M-COOH is the key intermediate to CO or HCOOH.…”
Section: Carbon Dioxide Reduction Reaction (Co2rr)mentioning
confidence: 99%
“…We propose that these studies inspire the exploration of the CISS effect in NRR, for example by using chiral molecules on NRR catalysts. [57] Copyright © 2022 American Chemical Society. c reproduced with permission.…”
Section: Nitrogen Reduction Reaction (Nrr)mentioning
confidence: 99%
“…The development of advanced energy conversion devices, such as fuel cells and water electrolyzers, is of essential importance for the great blossoming of the modern green and sustainable energy industry. , To carry forward the practical deployment of these energy systems, the requirements of active electrocatalysts with high activity and robust long-term durability should be satisfied for efficient fuel cells and water electrolyzers. , Oxygen electrocatalytic reactions, including the oxygen evolution reaction (OER) and oxygen reduction reaction (ORR), occur at the solid–liquid electrochemical interfaces of catalytic electrodes and greatly affect the overall efficiency and operational durability of industrial fuel cells and water electrolyzers due to their intrinsically sluggish kinetics. Therefore, it is very significant to completely understand the essential dynamics of solid–liquid electrochemical interfaces during electrocatalysis to rationally design, synthesize, and screen advanced oxygen electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[49][50][51][52][53] Additionally, the highly conjugated system of porphyrin-based molecules result in a number of invaluable properties, such as enhanced electronic conductivity and p-p stacking capabilities. [54][55][56][57] Although there exist several overarching reviews of CO 2 electrocatalysts including even more specic reviews on porphyrin/phthalocyanine catalysts, 50,51 a coverage of more recent developments in the eld is required. Herein, major advances involving the functionalization of porphyrin and phthalocyanine catalysts for electrochemical CO 2 RR will be recounted in detail with a focus on recent advances in heterogeneous electrocatalysts and the effects of various immobilization strategies on catalytic performance.…”
Section: Introductionmentioning
confidence: 99%